Mitior lex şi iluzia justei interpretări a atingerilor aduse intereselor financiare ale Uniunii Europene//Mitior lex and the illusion of just interpretation of impacts on the financial interests of the European Union - Bianca Maria DESPA RUSU; Elena Laura POSTOLACHE (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice)
This study aims to present an analysis over the effects of the prescription of criminal liability in cases concerning the offenses against the financial interests of the European Union, in light of the divergent interpretations outlined in national and European case law. In his quality as a protector of domestic law, as well as first magistrate in community law, the national judge is called upon to identify, through means of interpretation, a fair balance between the supremacy principle within European law and the internal standard of protection of fundamental rights. In order to prevent the establishment, through jurisprudential means and under the pretext of a legislative void, of a general standard of impunity, the latter risks decisively contributing to the erosion of the mitior lex principle. Within these limits, we inquire whether prescription further represents a real guarantee of the right to a fair trial.